Evaluation of poly(2-hydroxyethyl methacrylate) gels as drug delivery systems at different pH values - Ferreira, L. (2000)
Studies of dynamic and equilibrium swelling, structural characterisation and solute transport in swollen poly(2-hydroxyethyl methacrylate) gels (pHEMA) cross-linked with tripropyleneglycol diacrylate (TPGDA) were done for a wide range of TPGDA concentrations. The influence of the pH on these pHEMA properties was evaluated. In swelling studies it was found that in changing the pH from 6.5 to 12.0, a large increase in swelling occurred, from approximately 48 to 55%, for the lowest concentration of TPGDA (1 mol%), and from 40 to 80% for the highest concentration (10mol%). Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC) measurements were made after the equilibrium swelling of the gels at different pH values, to explain these results. The advantage of using these gels as controlled drug delivery systems is illustrated using salicylic acid (SA) as a model drug. The loading and the release of the SA were made at different pH values and the results obtained showed that it is possible to modulate the hydrogel performance by controlling an external factor, the pH at which the drug loading and release were performed.